Effectiveness Test of Several Bioinsecticides and Chemical Insecticides on the Mortality of Whitefly Pests (Bemisia tabaci) - Iqbal Prayuda; Rini Susanti; Zulaikha Mazlan (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Whitefly (Bemisia tabaci) is a major pest affecting various horticultural commodities and is challenging to control due to its high adaptability, rapid reproduction, and resistance to multiple chemical insecticides. This study aimed to compare the effectiveness of bioinsecticides and chemical insecticides on B. tabaci mortality. The research was conducted in the laboratory and greenhouse of the Malaysian Agricultural Research and Development Institute (MARDI) in September 2025, using a non-factorial Completely Randomized Design (CRD) with seven treatments and three replications. The seven treatments included Wood Vinegar, Paraffin Oil, Canola Oil, Neem Oil, Metarhizium anisopliae, Abamectin 1.8 EC, Diafenthiuron 250 SC, and water as the control. Applications were performed in the laboratory using the dipping method and in the greenhouse using the spraying method, with 30 B. tabaci nymphs per treatment and replication. Mortality was recorded at 24, 48, and 72 hours post-application. Laboratory results showed mortality rates of 24.44% for Wood Vinegar, 62.22% for Paraffin Oil, 71.11% for Canola Oil, 74.44% for Neem Oil, 70.00% for M. anisopliae, 38.89% for Abamectin, and 84.44% for Diafenthiuron. In the greenhouse, mortality rates were 16.67% for Wood Vinegar, 60.00% for Paraffin Oil, 67.78% for Canola Oil, 70.00% for Neem Oil, 62.22% for M. anisopliae, 30.00% for Abamectin, and 81.11% for Diafenthiuron 250 SC. Overall, among the chemical insecticides, Diafenthiuron exhibited the highest mortality and was the most effective treatment. Among the bioinsecticides, Neem Oil achieved the highest mortality. Based on these results, Neem Oil shows potential as a more environmentally friendly alternative control agent, while Diafenthiuron is suitable for use under conditions of high pest infestation.